2021
DOI: 10.1016/j.bbrep.2021.101133
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of JAK2 signaling produces immunomodulatory effect to preserve pancreatic homeostasis in severe acute pancreatitis

Abstract: JAK/STAT plays an important role in cytokine signal transduction and it is potentially involved in the proinflammatory response during the early phase of severe acute pancreatitis (SAP). However, whether JAK2 activity is upregulated and whether JAK2 inhibition plays a role in the maintenance of pancreatic homeostasis during SAP is incompletely understood. Here we show that JAK2/STAT3 activity is highly elevated in SAP and blockade of JAK2 by AG-490 protects against SAP-induced pancreatic inflammation and injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In most studies, however, activation of STAT3 stimulates macrophage M2 polarization. According to one study, JAK2/STAT3 activity was significantly increased in rats with severe acute pancreatitis, and JAK2 inhibition increased levels of cytokines (such as Foxp3, IL-10, and TGF-β) necessary for M2 macrophage polarization, leading to a reduction in the secretion of pro-inflammatory factors IL-6, IFN-γ, and TNF-α, which prevents pancreatic inflammation and damage ( 40 ). In animal models of myocardial ischemia/reperfusion injury and psoriasis, it was also demonstrated that inhibition of the JAK/STAT3 signaling pathway promoted macrophage M2 polarization, which in turn reduced pro-inflammatory factors and upregulated anti-inflammatory and pro-fibrotic factor levels, thereby favorably alleviating tissue inflammation and inhibiting tissue damage ( 41 , 42 ).…”
Section: Research On the Signaling Pathways Related To Stat3 Regulati...mentioning
confidence: 99%
“…In most studies, however, activation of STAT3 stimulates macrophage M2 polarization. According to one study, JAK2/STAT3 activity was significantly increased in rats with severe acute pancreatitis, and JAK2 inhibition increased levels of cytokines (such as Foxp3, IL-10, and TGF-β) necessary for M2 macrophage polarization, leading to a reduction in the secretion of pro-inflammatory factors IL-6, IFN-γ, and TNF-α, which prevents pancreatic inflammation and damage ( 40 ). In animal models of myocardial ischemia/reperfusion injury and psoriasis, it was also demonstrated that inhibition of the JAK/STAT3 signaling pathway promoted macrophage M2 polarization, which in turn reduced pro-inflammatory factors and upregulated anti-inflammatory and pro-fibrotic factor levels, thereby favorably alleviating tissue inflammation and inhibiting tissue damage ( 41 , 42 ).…”
Section: Research On the Signaling Pathways Related To Stat3 Regulati...mentioning
confidence: 99%
“…STAT pathway up-regulation inflammation (32,33) resulting in persistent and intensified inflammation (26). TLR9 is expressed in resident immune cells of the pancreas, which are predominantly represented by macrophages, and it is an important DAMP receptors upstream of inflammasome activation, and caspase-1, and NLRP3 inflammasome are required for the development of inflammation in AP (20,27).…”
Section: The Mechanism Of Acute Pancreatitismentioning
confidence: 99%
“…The incidence of AP continues to increase, causing single or multiple organ failure [7,8,9]. Pulmonary complications occupy a special place among the consequences of AP [1,6,13,14]. It has been established that in the pathogenesis of lung pathology, the morphofunctional state of type II alveolocytes plays an important role.…”
Section: Introductionmentioning
confidence: 99%